Research of Contemporary Violin Techniques in the Light of Kaija Saariaho’s Violin Works - Ezgi Yürümez (Konservatoryum)
In post-1950 music, an important aspect of the rapid, boundary-pushing development in musical composition in all its dimensions, which did not hesitate to break ties with the past, is the revolutionary transformation and progress in instrumental playing techniques.Works written for the violin, one of the most popular instruments of polyphonic music, vividly exemplify the progress in playing techniques in the contemporary period. Finnish composer Kaija Saariaho’s violin works, which contain a rich set of contemporary/extended violin techniques, provide the opportunity to clearly observe the usage and development of violin techniques in contemporary music. Kaija Saariaho, one of the prominent composers of the post-1950 generation, closely witnessed and/or was directly involved in significant milestones in the evolution of contemporary music in the second half of the 20th century, and became one of the leading figures of Finnish music worldwide. In this study, firstly, Kaija Saariaho’s life was examined in terms of the musical sources she was influenced by, then, the extended violin techniques in contemporary music were examined from a historical perspective, and finally, the extended violin techniques featured in the composer’s examined violin works were analyzed with quotations from selected passages and conveyed with notation examples.